The associations among genetic features, late gadolinium enhancement and prognosis in hypertrophic cardiomyopathy - Su, Wenhua; Wu, Hao; Chen, Chen; Zhang, Hongjiang; Yu, Qiuyue; Liang, Liwen; Huo, Qian; Lou, Hongbo; Che, Bingjun; Zhao, Yan; Dan, Juhua; Zhang, Hong (Frontiers in Cardiovascular Medicine, 2025)
AimsTo assess the combined prognostic value of genotype and late gadolinium enhancement (LGE) in hypertrophic cardiomyopathy (HCM) patients, including those with preserved left ventricular ejection fraction (LVEF).MethodsIn 135 HCM patients (age 52.43 ± 11.35 years, 79.26% male), whole-exome sequencing, echocardiography, and cardiac magnetic resonance (CMR) were performed. Major adverse cardiovascular and cerebrovascular events (MACCEs, e.g., cardiac death, progressive heart failure, sustained ventricular tachycardia/ventricular fibrillation, ICDs implantation, stroke, syncope, and atrial fibrillation) were analyzed over a median 15-month follow-up (IQR 9–36 months).ResultsPathogenic/likely pathogenic variants (G+) were identified in 50 (37%) patients, and LGE (L+) in 54 (40%). L+ patients exhibited worse clinical profiles: higher NYHA III–IV class (37% vs. 11%, P < 0.001), increased heart failure hospitalization (26% vs. 7%, P = 0.003), larger LV end-diastolic volume (median: 135, IQR: 125.25–213.00 vs. median: 126, IQR: 106.00–155.50, P = 0.004), lower LVEF (median: 55%, IQR: 39.75%–62% vs. median: 58%, IQR: 48%–65.5%, P = 0.012), and higher G+ prevalence (52% vs. 28%, P = 0.004). Both L+ (HR = 2.237, 95% CI: 1.178–4.247; P = 0.014) and G+ (HR = 1.872, 95% CI: 1.040–3.371; P = 0.037) independently predicted MACCEs after adjusting for age, NYHA class III–IV, LVOT obstruction and LVEF, adjusting for age, NYHA class III–IV, LVOT obstruction and LVEF. MACCE rates escalated across subgroups: G−/L− (22%), G+/L− (39%), G−/L+ (41%), and G+/L+ (63%) (P = 0.004). Among 89 patients with LVEF ≥150%, G+/L+ had the highest MACCE incidence (80% vs. 17% in G−/L−, P < 0.001).ConclusionThe combined assessment of genotype and late gadolinium enhancement significantly enhances risk stratification and prognosis prediction in hypertrophic cardiomyopathy patients, including those with preserved left ventricular ejection fraction, providing valuable insights for clinical decision-making.